ASSESSMENT OF PROPHYLACTIC MEDICATIONS PRESCRIBED FOR NAUSEA AND VOMITING AMONG POST-OPERATIVE SUBJECTS IN A TERTIARY CARE HOSPITAL, BENGALURU (Lex localis - Journal of Local Self-Government, 2025)
Background: Postoperative nausea and vomiting (PONV) is the most common complications seen within the first 24 hours following surgery under general anesthesia, with an incidence reported between 30-80% from earlier studies. Prophylactic management of PONV typicially involves administration of antiemetic such as ondansetron, metoclopramide, dexamethasone, scopolamine, granisetron and promethazine within 24 hours of post- surgery.Objectives: Primary objective was to describe prescription pattern of prophylactic medications used for PONV whereas, secondary objectives was to assess frequency, severity and effect of PONV.Methodology: A six-month prospective observational study was conducted at Aster RV Hospital after ethical approval from institutional human ethical committee of KLE college of pharmacy. Patient demographics, clinical data, and prescriptions were recorded. PONV risk was assessed using the APFEL score, with 24-hour postoperative follow-up and descriptive data analysis.Results: A total of 90 patients undergoing elective surgery under general anaesthesia were included, of which 61.1% were male and 38.9% female, with a mean age of 54.4 ± 2.6 years. Most subjects received a combination of general, inhalational, and regional anaesthesia. Ondansetron with dexamethasone was the most commonly administered prophylactic regimen (78.8%). PONV was reported in 61.1% of patients, occurring more frequently among males, non-smokers, and those with a history of motion sickness. Postoperative episodes were primarily managed with ondansetron, pantoprazole, and metoclopramide.Conclusion: The combination of ondansetron and dexamethasone was the most frequently prescribed and appropriate prophylactic regimen for PONV. Appropriateness of anti-emetics was found appropriate in most prescriptions as per Lexicomp database.  PONV occurred more commonly in Female, non-smokers and patients with a history of motion sickness. Most cases were effectively managed with standard antiemetics, and recovery was achieved within 24 hours.